2022
DOI: 10.5964/ejop.2889
|View full text |Cite
|
Sign up to set email alerts
|

How can students’ entrepreneurial intention be increased? The role of psychological capital, perceived learning from an entrepreneurship education program, emotions and their relationships

Abstract: Entrepreneurship education has become a major focus of interest for researchers and national policy makers to encourage students to pursue entrepreneurial careers. The research on entrepreneurship education–entrepreneurial intentions (EIs) has yielded mixed results, and indicates the need to focus on antecedents of EI. More precisely, the aim of this paper was to examine antecedents of students’ EI in French entrepreneurship education programs. Participants were 460 French university undergraduates. Structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 68 publications
0
11
0
3
Order By: Relevance
“…It is also important for all relevant stakeholders to include RMs in EE as RMs are found to be a significant source of SE that boost EE in driving EI. This study also depicted that SE is a strong antecedent for predictor EI, individuals who have received EE are more likely to pursue entrepreneurship as a career, to seek opportunities to start their own firms, and to engage in entrepreneurial activities effectively (Sancho et al., 2022; Chevalier et al., 2022).…”
Section: Discussionmentioning
confidence: 76%
“…It is also important for all relevant stakeholders to include RMs in EE as RMs are found to be a significant source of SE that boost EE in driving EI. This study also depicted that SE is a strong antecedent for predictor EI, individuals who have received EE are more likely to pursue entrepreneurship as a career, to seek opportunities to start their own firms, and to engage in entrepreneurial activities effectively (Sancho et al., 2022; Chevalier et al., 2022).…”
Section: Discussionmentioning
confidence: 76%
“…Individuals with new business intentions are more social, as they want to facilitate the market and people with new products and services to delight their needs. The intention of a new business can be turned into a new venture if the entrepreneurs are passionate and willing to work to perform well in the market [ 37 ]. The new venture can have a selective target market that would benefit the venture by generating more profit and remaining compatible in the market [ 38 ].…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
“…Entrepreneurs that are highly motivated to perform their tasks in the business environment are managing their business performance with optimism in an attractive way [ 45 ]. Entrepreneurial ventures working in the market require entrepreneurial optimism as it is necessary to take decisions related to the business [ 37 ]. Firms in any market face competition and other problems; however, deciding with optimism is a trait that helps businesses improve their performance with strategic decisions [ 46 ].…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
“…Still, the results of this study are consistent with research carried out by Margaça et al (2021), asserting that the impact of psychological capital on entrepreneurial intention was not direct but through financial, human, and social capital to influence the entrepreneurial intention of students. Then, the research conducted by Chevalier et al (2022) found that psychological capital did not directly affect entrepreneurial intention but had an indirect relationship. Also, the testing results of hypothesis 6 indicated that psychological capital did not mediate the social capital effect on the entrepreneurial intention of Universitas Syiah Kuala students.…”
Section: Suryani and Megawatimentioning
confidence: 99%